2008
DOI: 10.1167/iovs.07-1609
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma and On-Road Driving Performance

Abstract: This sample of patients with glaucoma with slight to moderate visual field impairment performed many real-world driving maneuvers safely. However, they were six times as likely as subjects with normal vision to have a driving instructor intervene for reasons suggesting difficulty with detection of peripheral obstacles and hazards and reaction to unexpected events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
115
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(132 citation statements)
references
References 33 publications
7
115
3
1
Order By: Relevance
“…Indeed, one study found that patients with glaucoma were less likely to see pedestrians on the side of the road during actual road tests. 48 This observation is supported by our lab-based studies using the driving hazard perception test (HPT), which is an element of the UK driving licence theory test. 52 In this test the 'learner driver' is shown a film of a real driving scene, seen from the perspective of the driver, with the task being to detect potential 'hazards': these are defined as something that would make the camera car take evasive action, such as braking for an oncoming cyclist or a pedestrian unexpectedly crossing the road.…”
Section: Aspects Of Visual Disability In Glaucomamentioning
confidence: 73%
See 2 more Smart Citations
“…Indeed, one study found that patients with glaucoma were less likely to see pedestrians on the side of the road during actual road tests. 48 This observation is supported by our lab-based studies using the driving hazard perception test (HPT), which is an element of the UK driving licence theory test. 52 In this test the 'learner driver' is shown a film of a real driving scene, seen from the perspective of the driver, with the task being to detect potential 'hazards': these are defined as something that would make the camera car take evasive action, such as braking for an oncoming cyclist or a pedestrian unexpectedly crossing the road.…”
Section: Aspects Of Visual Disability In Glaucomamentioning
confidence: 73%
“…[45][46][47] Glaucoma undoubtedly impacts on an individual when visual field loss causes the removal of a driving licence, and several studies have shown that certain glaucomatous visual field defects are not compatible with safe driving. 48,49 Interestingly, it has been demonstrated that UK patients perceive this particular potential outcome of their disease to be as serious to them as the long-term risk of blindness. 50 Patients are at greater risk of motor vehicle collisions and many patients stop driving even when the visual field loss is moderate.…”
Section: Aspects Of Visual Disability In Glaucomamentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using questionnaires and interview have revealed that glaucomatous patients feel their disease has an adverse impact on their ability to carry out everyday visual tasks such as driving, reading and searching for objects as well as their general ability to move from place to place (Green et al, 2002, Nelson et al, 1999, Hartmann and Rhee, 2006, Viswanathan et al, 1999. Studies of function in experiments have somewhat supported patient claims, demonstrating that individuals with glaucoma are impaired in several visual tasks compared with those with healthy vision of a similar age , Kotecha et al, 2009, Haymes et al, 2008, Smith et al, 2011. In addition, patients with even moderately damaged VFs are thought to be at an increased risk of falls and accidents, and in the case of certain more severe defects, glaucoma can ultimately lead to the removal of the patient's driving license (Haymes et al, 2007, White et al, 2006, Ramulu, 2009.…”
Section: Introductionmentioning
confidence: 98%
“…Unlike the typical visual field measurement situation when eyes are stationary, in the real world eye scanning will move the area of field loss around so that the obscured area of the scene changes over time. Recent on-road studies have demonstrated that even mild to moderate peripheral field loss results in measurable decrements in driving performance, though most participants were still considered safe drivers Haymes et al, 2008). In on-road studies evaluating drivers with hemianopia (a more severe field loss involving half the visual field on one side in both eyes), between 30% and 80% of participants failed the driving test (Tant et al, 2002;Tant, 2008;Wood et al, 2008).…”
Section: Introductionmentioning
confidence: 99%